β-Elemene: Mechanistic Studies on Cancer Cell Interaction and Its Chemosensitization Effect - Jiang, Ziyu; Jacob, Joe A.; Loganathachetti, Dinesh S.; Nainangu, Prasannabalaji; Chen, Baoan (Frontiers in Pharmacology, 2017)
Over the past decade, screening and identifying novel compounds for their biomedical applications has become an upcoming area of research. Identifying the molecular mechanisms of these compounds has become an integral part of anticancer research. β-elemene, a sesquiterpene, is renowned for its anticancer activity against a variety of cell lines. Recent studies on β-elemene have elucidated that it possesses anti-proliferative effect on cancer cells by creating an apoptotic trigger. Interestingly, it also induces protective autophagy in some cancerous cell lines and is less cytotoxic compared to other widely accepted chemotherapeutic agents. This provides an edge with the perception of limited toxicity to normal cells. This mini-review precisely focuses on the studies performed to identify the mechanism of anticancer activity of β-elemene against cancer cells of multiple origin. In accordance to the evaluation made by the studies mentioned, apoptosis has been identified to be most possible reason behind anticancer activity exerted by β-elemene against a variety of cancer cell lines. Cell cycle arrest and necrosis have been credited to be possible alternate mechanisms for the anticancer effect of β-elemene.